Therapeutic strategies, consequences and prospects of glucagon-like peptide-1 agonists - N.M. Bobok (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Social media shapes aesthetic trends in modern society significantly. Changes in requirements of aesthetic and plastic surgery based on these social trends have been repeatedly demonstrated. Social trends shape not only the requirements for appearance but also affect the pharmaceutical choice of the population. A clear example is the growing use of weight loss medicines. Glucagon-like peptide-1 (GLP-1) receptor agonists are widely prescribed for the treatment of type 2 diabetes and obesity, but they also affect a variety of physiological processes. Deep understanding of the effects of GLP-1 agonists on glucose metabolism, insulin secretion and gastrointestinal function is essential for optimal therapy selection and justification for using these medicines for weight management in patients without concomitant diabetes. An important feature of GLP-1 drugs is their ability to modulate appetite through effect on the hypothalamus, which makes them promising for the treatment of obesity. Studies show that these drugs affect not only carbohydrate metabolism but also the cardiovascular system and kidney function. However, their prolonged and unreasonable use may be accompanied by undesirable effects. Additional research and observations are needed on the long-term effects of GLP-1 on carbohydrate metabolism, weight management, gastrointestinal, liver, kidney function, and metabolic status of patients. Studying the mechanisms of action of of this group of agents will allow more accurately predict the individual effectiveness and risks of therapy. Accordingly, physicians need to understand the pharmacological effects of these drugs, as they will increasingly encounter patients who want to use or already take GLP-1 receptor agonists. Despite the fact that the media widely cover this issue, a comprehensive scientific description of the pharmacological effects, indications, prescribing features and potential consequences of GLP-1 agonists are relevant.